1993
DOI: 10.1084/jem.177.2.547
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 reduces the release of tumor necrosis factor and prevents lethality in experimental endotoxemia.

Abstract: SummaryBecause of its ability to efficiently inhibit in vitro cytokine production by activated macrophages, we hypothesized that interleukin (IL) 10 might be of particular interest in preventing endotoxininduced toxicity We therefore examined the effects of Ibl0 administration before lipopolysaccharide (LPS) challenge in mice. A marked reduction in the amounts of LPS-induced tumor necrosis factor (TNF) release in the circulation was observed after IL-10 pretreatment at doses as low as 10 U. Ibl0 also efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
344
1
12

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 760 publications
(376 citation statements)
references
References 24 publications
19
344
1
12
Order By: Relevance
“…Murine IL-10 was cloned and expressed as previously described (32). The biological activity of IL-10 was verified in an LPS-mediated lethal-shock model (27).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Murine IL-10 was cloned and expressed as previously described (32). The biological activity of IL-10 was verified in an LPS-mediated lethal-shock model (27).…”
Section: Methodsmentioning
confidence: 99%
“…Endotoxic shock and cutaneous inflammatory responses were enhanced in IL-10 knockouts (53,54). Likewise, blocking of endogenous IL-10 with neutralizing antibodies enhanced endotoxic shock, IgG immune complex-induced lung injury, and the severity of CIA (27,28,30). The latter study by Kunkel's group showed an increase in IL-10 at the mRNA and protein levels in joint tissues from the onset of arthritis, and accelerated expression of CIA was noted when anti-IL-10 treatment was started on day 24.…”
Section: Days After Immunizationmentioning
confidence: 96%
See 1 more Smart Citation
“…particularly due to inhibition of TNF- § production [10,11]. This demonstrates that the main in vivo function of IL-10 is to modulate the antimicrobial response which, when uncontrolled, can harm not only pathogens but as well the host itself.…”
Section: Introductionmentioning
confidence: 99%
“…ICAM-1 initiates adhesion and transendothelial migration of circulating leukocytes [42] . Evidence has also suggested that IL-10 may have a therapeutic potential in acute and chronic inflammatory disease [44] . Exogenous administration of recombinant IL-10 protects mice from lethal endotoxemia by reducing TNF-α release [44] .…”
Section: Discussionmentioning
confidence: 99%